The Effect of Compensation and Working Environment on the Performance and Organizational Commitment of PT Yulia Cosmetics Employees - Rambe, Saima; Nurul Dalimunte; Cut Sah Kha Mei Zsazsa (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research is a quantitative and qualitative research to determine the influence of compensation and work environment on the performance and organizational commitment of employees at PT. Yulia Cosmetics is a company that operates in a competitive business sector in an economy in the technological era, in meeting the challenges of technological competition and environmental changes, the compensation provided by PT. Yulia Cosmetics for employees exceeds the minimum minimum wage. If compensation and the work environment do not meet the needs of workers, the performance and commitment of the organization are not met, which will have an impact on employee work, resulting in the company experiencing a decline. The sample used was 32 employees of PT. Yulia Cosmetics Medan. Data were collected using a questionnaire, with the analysis technique used being multiple linear regression analysis with the help of the SPSS program. The results of the Rehabilitation Test show that the Compensation variable is 0.916, while the work environment is 0.863 and performance and organizational commitment is 0.898, which is significant at 0.000 <0.05, which shows that the career development variable has a positive and significant effect on employee job satisfaction, while the compensation variable has a calculated value of (5.180). > ttable (2.052) with a significance of 0.000 < 0.05 which indicates that the variable Compensation has a positive and significant effect on employee job satisfaction. Ftable (87.129>3.35) concludes that the independent variables, namely career development (X1) and compensation (X2) together have a positive and significant effect on the Employee Job Satisfaction variable (Y) at the Grand Impression Hotel Medan. The analysis shows that career development has an effect on employee job satisfaction and compensation has an effect on employee job satisfaction and career development and compensation have a simultaneous effect on employee job satisfaction